Development of ADDIE model-based busy book media to improve children's fine motor skills - Selvi Widiyana; Shofiyanti Nur Zuama; Hamzia Marie; Andi Agusniatih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Early childhood fine motor skills need early stimulation because they form the foundation for everyday academic and independent skills such as writing, buttoning, and tying ropes. Observations at North Palu State Kindergarten found that some children aged 5-6 years still have difficulty with activities that require hand-eye coordination, such as buttoning, opening zippers, and tying ropes. This condition shows the need for interesting learning media that aligns with children's characteristics to optimally stimulate fine motor development. This research aims to develop a suitable and effective Busy Book media in stimulating children's fine motor skills. The method used is Research and Development (R&D) with the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The study subjects were 15 children in the B1 group of North Palu State Kindergarten, selected using purposive sampling based on the criteria of children aged 5-6 years and actively registered in class B1. Data collection used observation, interviews, documentation, expert validation questionnaires, and children's fine motor tests before and after media use. The results showed that the Busy Book media fell into the very feasible category based on validation by material and media experts, with an average percentage of 98.68%. The effectiveness test results showed that children's fine motor skills increased from an average score of 56.47 in the pretest to 87.05 in the posttest after using the Busy Book media. Thus, Busy Book media can serve as an effective alternative learning medium to support fine motor development in early childhood. This media can also serve as an alternative for PAUD teachers to provide interesting, interactive, and appropriate learning in accordance with the characteristics of child development.